MHC class II genotype‐by‐pathogen genotype interaction for infection prevalence in a natural rodent‐Borrelia system. (9th August 2022) - Råberg, Lars; Clough, Dagmar; Hagström, Åsa; Scherman, Kristin; Andersson, Martin; Drews, Anna; Strandh, Maria; Tschirren, Barbara; Westerdahl, Helena
Abstract: MHC genes are extraordinarily polymorphic in most taxa. Host‐pathogen coevolution driven by negative frequency‐dependent selection (NFDS) is one of the main hypotheses for the maintenance of such immunogenetic variation. Here, we test a critical but rarely tested assumption of this hypothesis—that MHC alleles affect resistance/susceptibility to a pathogen in a strain‐specific way, that is, there is a host genotype‐by‐pathogen genotype interaction. In a field study of bank voles naturally infected with the tick‐transmitted bacterium Borrelia afzelii, we tested for MHC class II ( DQB ) genotype‐by‐ B. afzelii strain interactions for infection prevalence between 10 DQB alleles and seven strains. One allele (DQB*37) showed an interaction, such that voles carrying DQB*37 had higher prevalence of two strains and lower prevalence of one strain than individuals without the allele. These findings were corroborated by analyses of strain composition of infections, which revealed an effect of DQB*37 in the form of lower β diversity among infections in voles carrying the allele. Taken together, these results provide rare support at the molecular genetic level for a key assumption of models of antagonistic coevolution through NFDS.